Research Advances on Therapeutic Approaches to Congenital Central Hypoventilation Syndrome (CCHS) - Di Lascio, Simona; Benfante, Roberta; Cardani, Silvia; Fornasari, Diego (Frontiers in Neuroscience, 2021)
Congenital central hypoventilation syndrome (CCHS) is a genetic disorder of neurodevelopment, with an autosomal dominant transmission, caused by heterozygous mutations in the PHOX2B gene. CCHS is a rare disorder characterized by hypoventilation due to the failure of autonomic control of breathing. Until now no curative treatment has been found. PHOX2B is a transcription factor that plays a crucial role in the development (and maintenance) of the autonomic nervous system, and in particular the neuronal structures involved in respiratory reflexes. The underlying pathogenetic mechanism is still unclear, although studies in vivo and in CCHS patients indicate that some neuronal structures may be damaged. Moreover, in vitro experimental data suggest that transcriptional dysregulation and protein misfolding may be key pathogenic mechanisms. This review summarizes latest researches that improved the comprehension of the molecular pathogenetic mechanisms responsible for CCHS and discusses the search for therapeutic intervention in light of the current knowledge about PHOX2B function.